2008
DOI: 10.1111/j.1745-7262.2008.00385.x
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivoantioxidant effects of D-004, a lipid extract fromRoystonea regiafruits, on rat prostate tissue

Abstract: Oral treatment with D-004 reduced MDA and carbonyl groups dose-dependently and markedly in normal and T-injected rats. These findings show that D-004 given at doses effective to prevent prostate hyperplasia also produces antioxidant effects in the prostate tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
3
11
0
Order By: Relevance
“…The present results are consistent with previous reports of the antioxidant effects of D-004 [25][26][27][28] and SP [28], and demonstrate, for the first time, that D-004 may decrease IPSS and to produce antioxidant effects in men with BPH that were comparable to those of SP. Both groups had similar baseline characteristics, so that they were homogeneous for comparisons.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The present results are consistent with previous reports of the antioxidant effects of D-004 [25][26][27][28] and SP [28], and demonstrate, for the first time, that D-004 may decrease IPSS and to produce antioxidant effects in men with BPH that were comparable to those of SP. Both groups had similar baseline characteristics, so that they were homogeneous for comparisons.…”
Section: Discussionsupporting
confidence: 82%
“…The effect of D-004 on this variable, however, should not be interpreted as a proof of efficacy, as recent reports show controversial results of the use of this marker. The lack of effect of SP on this variable agrees with other reports [46].The treatments were well tolerated, consistent with previous data [25][26][27][28]40]. Safety indicators and sexual performance were not impaired by the treatments, which agree with previous reports on SP [11,12,46], and being the first report on this matter for D-004.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…D-004 has a composition similar, although not identical, to that of saw palmetto (a lipid extract of Serenoa repens used to treat BPH at doses from 160 to 320 mg day −1 ) [28,29]. Experimental data have shown that D-004 extracts were more effective than saw palmetto extracts in reducing prostate enlargement [20][21][22]27] and that the doses effective in eliciting such an effect were also able to reduce oxidative markers in rat plasma and prostate [26,27]. In light of this, we expected that the oral administration of D-004 at a dose similar to a therapeutic dose of saw palmetto would produce antioxidant effects in plasma oxidative markers of healthy men.…”
Section: Treatments and Randomizationmentioning
confidence: 99%
“…D-004, given orally, has been shown to decrease T-induced prostate hyperplasia in rodents [20][21][22] and to inhibit rat prostate 5α reductase in vitro [23]. In addition, D-004 antagonized α1-adrenoreceptor-mediated responses [24,25] in rats and reduced the oxidation of LP and protein in prostate tissue of both normal and T-treated rats [26,27]. However, the antioxidant effects of D-004 have not yet been shown in humans.…”
Section: Introductionmentioning
confidence: 99%